STUDI HULL FORM KAPAL BARANG-PENUMPANG TRADISIONAL DI DANAU TOBA SUMATERA UTARA - Manik, Parlindungan; Hadi, Eko Sasmito (Department of Naval Architecture - Diponegoro University, 2008)
This thesis concerns to the study of traditional cargo-passenger ship's hull in Danau Toba, North Sumatera. Most of the ship in that territory is built in a traditional method by the community near the lake and with the descending ancient method for years. The re-drawing process of the ship is using Delftship software. As a result of this study report, this software could give the data of hydrostatic, resistance, stability and the rolling period and also the ship moving in water. This information could be used as a suggestion to make the mutual standard of the ship's body form which is appropriate to the condition in Danau Toba. According to the calculation and analysis by using Delftship software, it could give the result that suitable with the main dimension ratio of KM. Horas Ronita Nainggolan. KM. Horas Ronita Nainggolan is classified as a harbor tug boat based on her main dimension. She has the maximum speed at 8,7 Knots, there is increased ship resistance for 0,02025 % KN at 8 Knots. In the rain condition, she is not really good in stability with the passengers and freights are near the fore peak of the ship (the position of the ship is almost in even keel), but she has a better stability in sunny weather. At the ship moving case, the greatest heaving motion is responded by the ship in the condition of slight water wave heading 135°, greatest pitching motion is responded by the ship in the condition of water wave heading 45°, and the greatest rolling motion is responded by the ship in the condition slight water wave heading 45°